ANALISIS KEBIJAKAN RELAKSASI PAJAK PEMPROV DKI JAKARTA ATAS DAMPAK PANDEMI COVID-19 DARI PERSPEKTIF ASAS THE FOUR MAXIM - Dwi Heru Setiawan (Universitas Janabadra, 2020)
The COVID-19 pandemic that occurred in almost all parts of the world had a huge impact on the aspects of human life, especially in the economic field. One of the sectors affected by the economic sector is the tax sector, namely the decline in tax revenue. In this article, we will discuss further regarding the tax relaxation policies taken by the Regional Government to increase tax revenue and to empathize with the economic conditions of the people affected by the COVID-19 Pandemic. Next, we will examine how the relaxation policy is from the point of view (perspective) of the four maxim principle. The research method used in this paper is normative legal research using primary and secondary legal materials, and the data collection method used is literature study. From the research results, it is known that several policies of the DKI Jakarta Provincial Government are related to the provision of local tax relaxation and how the four maxim principle perspective on the regional tax relaxation policy.Keywords: COVID-19, Local Taxes, Tax Relaxation, The Four Maxim Principle